2019
DOI: 10.1088/1742-6596/1356/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Wind-wave directional effects on fatigue of bottom-fixed offshore wind turbine

Abstract: The current trend for offshore wind energy is that larger turbines are placed on monopile foundations at increasing water depth. This requires larger foundations, increasing the importance of hydrodynamic loading. It is well established that wave loads perpendicular to the wind direction are important for the fatigue damage in monopile foundations. However, this is normally only taken into account considering wind-wave misalignment. In this paper, the effect of assuming short-crested waves in design calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A slightly modified version of the DTU 10-MW reference turbine is used in the present study. 30 The modifications on the turbine itself are performed by Bachynski and Ormberg, 31 while Sørum et al 32 designed the monopile foundation. The wind turbine, foundation and soil characteristics used in the current study are equal to the base model of Sørum et al, 32 with the exception of a slightly larger monopile diameter.…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A slightly modified version of the DTU 10-MW reference turbine is used in the present study. 30 The modifications on the turbine itself are performed by Bachynski and Ormberg, 31 while Sørum et al 32 designed the monopile foundation. The wind turbine, foundation and soil characteristics used in the current study are equal to the base model of Sørum et al, 32 with the exception of a slightly larger monopile diameter.…”
Section: Responsementioning
confidence: 99%
“…30 The modifications on the turbine itself are performed by Bachynski and Ormberg, 31 while Sørum et al 32 designed the monopile foundation. The wind turbine, foundation and soil characteristics used in the current study are equal to the base model of Sørum et al, 32 with the exception of a slightly larger monopile diameter. The water depth is 30 m and the monopile extends 43 m below the mud line.…”
Section: Responsementioning
confidence: 99%
“…Despite this, wave spreading has received little attention in the research community, with the authors knowing only three studies. 21,22,75 The effect of the soil model is also significant, demonstrating the need for accurate modelling of soil damping and stiffness. In terms of the coherence model, most models used today are developed for small diameter rotors with onshore wind conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Including short‐crested waves was found to reduce the fatigue damage. Sørum et al 22 showed that short‐crested waves may result in both a higher and lower fatigue damage than long‐crested waves, depending on the monopile design. Bachynski and Ormberg 23 showed that wave diffraction becomes more important as monopile diameters increase.…”
Section: Introductionmentioning
confidence: 99%
“…Current standards adopted the conservative assumption of the unidirectionality of environmental forces which represents a worst-case scenario. Such an assumption can adversely affect the accuracy of fatigue analysis, reliability analysis and also the dynamic analysis of MPOPs with complex geometries, e.g., the direct attachment of an aquaculture cage to the foundation of an OWT) ( Sørum et al, 2019 ).…”
Section: Reliability Analysis Of the Integrated Systemmentioning
confidence: 99%